Prevalence of Left Ventricular Hypertrophy in End Stage Renal Disease Patients on Maintenance Hemodialysis : Ventricular Hypertrophy in End Stage Renal Disease - Naz, Afreen; Das, Bhagwan; Memon, Sughand; Sanjay, .; Memon, Rafia; Kumar, Kishor (Pakistan Journal of Health Sciences, 2023)
Among the hemodialysis population, left ventricular hypertrophy (LVH) is becoming a major cause of cardiovascular death, mainly due to myocardial infarction, heart failure, and arrhythmias. Objective: To determine the frequency of left ventricular hypertrophy in ESRD patients on maintenance hemodialysis. Methods: The Descriptive Cross-sectional study was conducted at Department of Nephrology, Liaquat University of Medical and Health Sciences Jamshoro. All patients above 18 years of age and below 65 years of age of both gender having end stage renal disease on maintenance hemodialysis with 3 months or more of maintenance hemodialysis were consecutively enrolled. On dialysis free day patients meeting inclusion criteria was sent for Trans Thoracic Echocardiography. Measurements was taken as inter-ventricular septal thickness, left ventricular end-diastolic diameter and left ventricular posterior wall thickness through parasternal long axis or short axis just distal to the tip of mitral valve leaflet. Results: The mean age of the patients was 53.54 ± 11.63 years. There were 72 (61.5%) males and 45 (38.5%) females. The mean duration of hemodialysis was 5.61 ± 0.97 months. The mean duration of ESRD was 7.23 ± 0.78 months. Type 2 diabetes mellitus was found in 73 (62.4%) and hypertension in 71 (60.7%) patients. The frequency of left ventricular hypertrophy was found in 53 (45.3%) patients. Conclusions: The frequency of left ventricular hypertrophy was found to be 45.3% in ESRD patients on maintenance hemodialysis